Diffuse Pancreatic Carcinoma with Hepatic Metastases - Hoang Quan Nguyen; Ngoc Trinh Thi Pham; Van Trung Hoang; Hoang Anh Thi Van; Chinh Huynh; Duc Thanh Hoang (Case Reports in Oncological Medicine)
Pancreatic cancer is one of the seven leading causes of cancer death worldwide. Diffuse pancreatic carcinoma is very rare and underreported in the literature. Many advances have been made in the diagnosis and management of pancreatic cancer. However, most pancreatic cancer cases are detected at the terminal or metastatic stages. Therefore, timely diagnosis and therapeutic management are desirable goals for this disease. Although the proliferation of pancreatic cancer has been reduced by intervention, more work is needed to treat and prevent the disease. The purpose of this article is to present a case of a 54-year-old male with pancreatic cancer and to review the epidemiology, diagnosis, management, and prevention of pancreatic tumors in general as well as pancreatic carcinoma in particular.